2008
DOI: 10.1086/592249
|View full text |Cite
|
Sign up to set email alerts
|

Biased Genotype Distributions ofCandida albicansStrains Associated with Vulvovaginal Candidosis and Candidal Balanoposthitis in China

Abstract: The results suggest the existence of vaginopathic C. albicans strains with enhanced virulence and tropism for the vagina and the high possibility of sexual transmission of genital C. albicans infection. Identification of specific genotypes that correlate with severity of VVC is also of diagnostic and therapeutic significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
37
2
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 33 publications
3
37
2
3
Order By: Relevance
“…2. The clustering of C. albicans isolates based on ERG11 sequence analysis is in agreement with that shown in a previous study of ours based on sequence analysis of three housekeeping genes (11). The correlated variations of different gene sequences with CAI genotypes confirm the merit of C. albicans strain typing based on CAI polymorphism.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…2. The clustering of C. albicans isolates based on ERG11 sequence analysis is in agreement with that shown in a previous study of ours based on sequence analysis of three housekeeping genes (11). The correlated variations of different gene sequences with CAI genotypes confirm the merit of C. albicans strain typing based on CAI polymorphism.…”
Section: Discussionsupporting
confidence: 90%
“…These two dominant genotypes were rarely found among isolates from extragenital sites (11). In addition, the distribution of the dominant genotypes correlated positively with the severity of VVC (8,11). These results suggested that C. albicans isolates with genotypes CAI 30-45 and CAI 32-46 might be more virulent and/or more resistant to the commonly used azole drugs than those with other genotypes as causative agents of vaginal infection.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…When analyzing the genetic diversities of human fungal pathogens, for instance, Histoplasma capsulatum (25), Candida albicans (26), Aspergillus fumigatus (23), and Cryptococcus neoformans (27), it has been demonstrated that SNP analyses were highly discriminative in these species. Based on multilocus sequence analyses (MLSAs), genetic diversity in plant-pathogenic fungi was also reported for Magnaporthe grisea and Ustilaginoidea virens (28,29).…”
mentioning
confidence: 99%